Development of a quick serum IL-6 measuring system in rheumatoid arthritis. (July 2017) - Koyama, Kensuke; Ohba, Tetsuro; Ishii, Kentaro; Jung, Giman; Haro, Hirotaka; Matsuda, Kenichi
Abstract: Objective: Interleukin-6 (IL-6) plays a crucial role in the pathogenesis of rheumatoid arthritis (RA). Both fulfillment of remission criteria and assessment of other methods of evaluation of RA are important for preventing joint damage progression. Measurement of serum IL-6 concentrations has been reported to be useful for monitoring RA disease activity. However, it takes at least 4–5 h to measure serum IL-6 concentrations using traditional methods, which limits its utility during routine assessment in daily clinical practice settings. We established a novel method that enables measurement of serum IL-6 within 24 min and requires a very small blood volume. We investigated the accuracy and efficacy of this system in RA patients. Methods: One hundred fifty blood samples collected from 76 patients were measured using the two systems. We first developed the prototype of the Human IL-6 RAYFAST. Then, we examined the correlation between the prototype RAYFAST and chemiluminescent enzyme immunoassay (CLEIA) methods. Finally, we compared IL-6 concentrations and clinical parameters using both systems. Results: The correlation between RAYFAST (x) and CLEIA (y) for IL-6 was y = 0.895x − 5.94, r = 0.941 (p < 0.0001). Serum IL-6 concentrations in RAYFAST correlated with DAS28-CRP (r = 0.372, p < 0.05) and DAS28-ESR (r = 0.397, p < 0.01). Serum IL-6 concentrations in CLEIA correlated with DAS28-CRP (r = 0.313, p < 0.001) and DAS28-ESR (r = 0.353, p < 0.001). Conclusion: This new cytokine quick measure system is as accurate as CLEIA methods. Serum IL-6 concentrations can be measured in 24 min using the prototype RAYFAST. It might be usable in the daily clinical practice setting, thereby contributing to improved RA management.